1993
DOI: 10.1159/000126482
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine Potentiates the Growth Hormone (GH) Response to GH-Releasing Hormone in Norepinephrine Synthesis-Inhibited Rats: Evidence for an Alpha-2-Adrenergic Control of Hypothalamic Release of Somatostatin

Abstract: The aim of this study was to investigate whether central α2-adrenergic pathways act, in rats, by inhibiting somatostatin (SS) release, as it has been postulated to occur in other species. The growth hormone (GH) responses to GH-releasing hormone (GRF, 3 µg/kg i.v.) or clonidine (CLO, 100 µg/kg, i.v.), either given alone or in combination, were tested in male rats in which norepinephrine synthesis had been previously blocked with the dopamine-β-hydroxylase inhibitor diethyldithiocarbamate (DDTC, 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
(54 reference statements)
2
19
0
Order By: Relevance
“…On the other hand, there are some reports which proposed that the stimulatory effect of clonidine, an a2-adrenoceptor agonist, on GH release is mainly exerted by inhibiting the hypothalamic SRIF release in rats [20][21][22] and man [23]. But the study by Magnan et al in sheep [24] has demonstrated that clonidine acts centrally to stimulate GH and that this effect is mediated through changes in GHRH release into hypophysial portal blood.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are some reports which proposed that the stimulatory effect of clonidine, an a2-adrenoceptor agonist, on GH release is mainly exerted by inhibiting the hypothalamic SRIF release in rats [20][21][22] and man [23]. But the study by Magnan et al in sheep [24] has demonstrated that clonidine acts centrally to stimulate GH and that this effect is mediated through changes in GHRH release into hypophysial portal blood.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma GH levels and pituitary GH content were determined by RIA as previously described (Lima et al, 1993). Pituitary homogenates were diluted 1:5000 for determination.…”
Section: Radioimmunoassaysmentioning
confidence: 99%
“…Bloch et al (1984) showed that MSG treatment results in the complete loss of growth hormone releasing factor (GRF)-immunoreactive cell bodies within this nucleus and provokes a selective disappearance of GRF-immunoreactive fibres in the median eminence of rats. This technique has routinely been practised to produce functionally hypopituitary animals (Lima et al, 1993) for studies of short-term growth (Hermanussen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For the GH determinations, the reagents provided by the NIADDK (Baltimore, MD, USA) were used as previously described (Lima et al 1993). The iodination of rat GH I-6 was performed using lactoperoxidase (Thorell & Johansson 1971).…”
Section: Hormone Determinationmentioning
confidence: 99%